2012
DOI: 10.1161/atvbaha.112.254144
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Exposure of Sites in von Willebrand Factor for Glycoprotein Ib Binding and ADAMTS13 Cleavage

Abstract: Objective-Platelet-bound von Willebrand factor (VWF) was recently demonstrated to be a better substrate for ADAMTS13, suggesting that 1 conformational change exposes both the glycoprotein Ibα binding site in the A1 domain and the ADAMTS13 cleavage site in the A2 domain. Because ristocetin induces VWF to bind glycoprotein Ibα in the absence of shear stress, we evaluated whether it could also enhance ADAMTS13 proteolysis of VWF. Methods and Results-We used several VWF sources: plasma, purified plasma VWF, recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Additionally, the interaction between platelet vimentin and the gain-of-function A1(R1450E) A2A3 mutant, which binds to vimentin (this study) and GPIba in a ristocetin-independent manner, 9,18 was efficiently reduced by the anti-vimentin antibody. These outcomes are consistent with the information that VWF exposes the cleavage site for ADAMTS-13 in the A2 domain on a conformational change induced by ristocetin, 35 indicating that vimentin interacts specifically with the active form of VWF.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, the interaction between platelet vimentin and the gain-of-function A1(R1450E) A2A3 mutant, which binds to vimentin (this study) and GPIba in a ristocetin-independent manner, 9,18 was efficiently reduced by the anti-vimentin antibody. These outcomes are consistent with the information that VWF exposes the cleavage site for ADAMTS-13 in the A2 domain on a conformational change induced by ristocetin, 35 indicating that vimentin interacts specifically with the active form of VWF.…”
Section: Discussionsupporting
confidence: 88%
“…This notion is supported by the report by Hulstein et al [27] that a nanobody made against the VWF A1 detected a very small amount of VWF in blood samples from healthy subjects, but a significantly increased amount of VWF in patients with TTP. It is also supported by our finding that the VWF-fH interaction was enhanced in the presence of ristocetin, which is known to induce an active conformation of VWF [21,28]; and is consistent with a recent report by Turner et al, who showed binding of fH to ULVWF strings secreted by, and anchored to, endothelial cells [29]. Second, VWF exists in the blood as multimers of different sizes and a calculated binding affinity for such a heterogeneous ligand may be accurate only for VWF of a particular size.…”
Section: Discussionsupporting
confidence: 76%
“…The stretching force ensures, however, that the VWF is activated for platelet binding predominantly before deactivation through cleavage. In this respect, the interactions between A1 and A2 may also serve to clarify the role of ristocetin, coupling platelet binding and ADAMTS13 cleavage (48).…”
Section: Main Orientational Modes Of the Autoinhibited Statementioning
confidence: 99%